The Brain and History. On the Reading Brain and the Naivety of Biological Reductionism - Rudnicki, Cezary (Sensus Historiae, 2025)
In 2009, an influential French neurobiologist Stanislas Dehaene published a monograph devoted to the neurobiology of reading. The book not only presents the results of research conducted in previous decades by psychologists and neuroscientists, but also aims to explain the origins of writing as a cultural invention. It includes an entire chapter devoted to the ‘neurohistory’ of writing and another one explaining why only the human brain was capable of creating it. Using a reductionist approach strongly inspired by sociobiology, it presents the history of writing as an evolution driven by the mechanism of cultural selection. The aim of this article is to confront the theses put forward by Dehaene with the results of research conducted by professional historians. Due to the scope of the subject of the history of writing, I will limit myself exclusively to the issue of Mesoamerican glyphs depicting faces. This means discussing a thesis that appears only marginally in Dehaene’s work. However, in my opinion, it encapsulates the most important elements of his theory.